How Japanese Popular Culture Has Been Studied in Indonesia, 2003-2023: A Narrative Review and Agenda for Future Research - Umoro, Anisa Ledy (KIRYOKU, 2025)
This paper presents a narrative review of Indonesian academic discourse on Japanese popular culture and examines how this field has developed over the past twenty years. Using selected keyword searches in academic databases and journals, 97 relevant articles published between 2003 and 2023 have been identified. These articles are thematically coded and analyzed to map prevailing research trajectories. The review reveals four dominant themes: (1) cinema and anime, (2) audience and reception, (3) soft power and cultural diplomacy, and (4) representation and identity. This mapping highlights both well-established areas of study and underexplored topics that require further attention. By identifying gaps in the existing literature and suggesting new directions for inquiry, the paper contributes to a deeper understanding of how Japanese popular culture has been studied in Indonesia. It also provides a foundation for future scholarship and a resource for those seeking to expand this field.